Strategi Pembelajaran Al-Quran di Lembaga Pondok Anak dan Tahfidzul Qur’an Pondok Pesantren Al-Qodiri 1 Jember - Andre Fanani; Syaiful Rizal (Jurnal Al-Fatih, 2026)
Effective Al-Qur'an learning strategies are essential to improve students' recitation quality and memorization in tahfidz institutions. This study aims to analyze the Al-Qur'an learning strategies implemented at the Lembaga Pondok Anak dan Tahfidzul Qur'an, Pondok Pesantren Al-Qodiri 1 Jember, focusing on learning planning, implementation, evaluation, and efforts to overcome learning challenges. This research employed a qualitative case study approach involving the head of the institution, teachers (ustadz and ustadzah), and students. Data were collected through observation, interviews, and documentation and analyzed using data condensation, data display, and conclusion drawing with source and technique triangulation. The findings reveal that Al-Qur'an learning is systematically implemented through the integration of binnadzor, ziyadah, and muroja'ah methods, supported by continuous evaluation of recitation accuracy, tajwid, fluency, and memorization retention. Students' fatigue resulting from formal school activities was identified as the main challenge and was addressed through continuous motivation, personal guidance, educational games, rewards, and intensive supervision. These integrated strategies effectively improve students' Qur'anic reading quality, memorization retention, and learning motivation, demonstrating their effectiveness in supporting Al-Qur'an learning.